Mechanosensitivity of myoblast-derived extracellular vesicles: implications for skeletal muscle regenerative therapeutics - Williams, Katherine B., author; Ehrhart, Nicole, advisor; Hamilton, Karyn L., advisor; LaRocca, Thomas J., committee member; Duval, Dawn, committee member (Colorado State University. Libraries, 2025)
Skeletal muscle regenerative capacity and function declines with advancing age. This contributes to poor recovery following surgery or injury, and to age-related muscle loss and dysfunction (i.e. sarcopenia). Extracellular vesicles (EVs) are membrane-bound vesicles that regulate intercellular signaling through the delivery of complex cargo including RNAs, proteins, and lipids. Over the past decade, EVs have emerged as promising biologic therapeutics for musculoskeletal repair due to their ability to deliver bioactive cargo to recipient cells, recapitulating many of the benefits of mesenchymal stromal cells. However, strategies to enhance EV therapeutic potential and to optimize their cargo for regeneration remain limited. Mechanical forces are a potent regulator of skeletal muscle development and homeostasis. Key processes for effective muscle regeneration, including muscle stem (i.e. satellite cell) and progenitor cell (myoblast) quiescence, activation, proliferation, and differentiation, are all impacted by mechanical signaling. EV biogenesis and function are also affected by mechanical cues. Because EV composition and function are highly dependent on the physiology and environment of the parent cell, we hypothesized that applying mechanical strain to myoblasts will modulate their EV cargo and function to enhance myogenesis and muscle regeneration. Broadly, this dissertation investigates how mechanical strain alters the production, microRNA (miRNA) cargo, and regenerative capacity of EVs derived from myoblasts, with the overarching goal of optimizing EV-based therapies for aged muscle regeneration. Chapter 1 discusses the potential of EVs as an alternative to mesenchymal stromal cells for regenerative medicine, the impact of aging on EV biogenesis, and mechanical cues as a tunable factor to modulate EV cargo and function. Chapter 2 demonstrates that mechanical strain applied to C2C12 myoblasts increases EV production, enhances proliferation and differentiation of naïve myoblasts receiving EVs derived from strained myoblasts, and modulates EV miRNA cargo. In Chapter 3, we describe an optimized protocol to isolate and expand primary C57BL/6 murine myoblasts, characterize the EVs they produce, and compare the effects of EVs derived from bone marrow MSCs to EVs derived from primary myoblasts on myoblast proliferation. Chapter 4 investigates the impact of mechanical strain on primary myoblast EV miRNA cargo, as well as the impact of mechanically strained primary myoblast EVs on gene expression, proliferation, and differentiation in recipient myoblasts. Finally, Chapter 5 evaluates the effects of strained myoblast-derived EVs on in vivo muscle regeneration in an aged mouse model of muscle injury. Together, this research demonstrates that mechanical strain is a powerful tool to modulate myoblast EV miRNA cargo and myogenic function, possibly enhancing the therapeutic potential of myoblast-derived EVs to accelerate recovery of aged muscle function following injury. This work advances our understanding of EV biology in the context of optimizing biologic therapeutics for muscle regeneration and muscle aging.
Keywords: extracellular vesicles; muscle; regeneration; mechanical signaling; aging; myogenesis